Production and Performance Test of Biodiesel Produced from Waste Cooking Oil - Setiawan, Yosua; Sutanto, Hadi; Leman, Abdul Mutalib (Cylinder : Jurnal Ilmiah Teknik Mesin, 2024)
Biodiesel has become an important source as a subtitution fuel for diesel engines. As an alternative fuel for diesel engines, it is becoming increasingly important due to diminishing fossil fuel reserves and the environment consequeness of exhaust gases from petroleum fuelled engines therefore, it needs to be further investigated how biodiesel blend percentage could affect the performance and emission of diesel engine. Waste cooking oil (WCO) is one of the raw material for Biodiesel. WCO that has been converted into biodiesel is made using esterification and transesterification methods. Then, biodiesel is mixed until it has the composition of B20, B30 and B50. The mixture is then tested for performance and emissions. In testing, B30 did not have a significant decrease in performance but the emission test results (opacity) were higher than B20. B50 has a significant decrease in performance when compared to B20, but has the lowest opacity test results.